Biology of the schistosome genus Trichobilharzia - Horák, P; Kolárová, L; Adema, C M (Advances in parasitology, 2002)
Trichobilharzia is the largest genus within the family Schistosomatidae, covering over 40 species of avian parasites. To clarify the existing confusion in the systematics of the genus, we recommend combining knowledge of life cycles and developmental stages, snail/bird hosts, cytogenetical and molecular data together with morphological criteria for the characterization of particular species. The high specificity of Trichobilharzia for the intermediate host is a likely reflection of the ability to avoid the internal defence of specific snails. The spectrum of final hosts (birds) seems to be much wider. The infection of birds--trichobilharziasis--may lead to considerable tissue injuries, caused by eggs of the parasite or migration of immature/mature worms through the body. Most Trichobilharzia (visceral species) migrate through the viscera of the host, but nasal species display a neurotropic mode of migration. Due to a low specificity of penetrating cercariae, mammals (including humans) can be attacked. This leads to cercarial dermatitis, predominantly in sensitized hosts. Experimental infections indicate that Trichobilharzia never mature in an incompatible (mammalian) host. However, not all cercariae and schistosomula are necessarily trapped and eliminated in the skin, and parasites may migrate throughout the viscera and the nervous system of mammals. These findings suggest that the pathogenicity of Trichobilharzia may have been underestimated in the past and health risks associated with trichobilharziasis need to be studied further.
Keywords: Snails; Prevalence; prevalence; Trematode Infections; Birds; Schistosomatidae; Dermatitis; dermatitida; hlemýždi; Life Cycle Stages; Nasal Cavity; zvířata; Humans; nosní dutina; Host-Parasite Interactions; interakce hostitele a parazita; ptáci; stadia vývoje; lidé; infekce červy třídy Trematoda; Animals